Сумма делителей в кольце целых гауссовых чисел - Синявский, О.В. (Український математичний журнал, 2001)
Будується асимптотична формула суматориої функції для σa(α), де σa(α) — сума a−x степенів норм дільників цілого гауссового числа α на арифметичній прогресії α≡α₀(modγ) і у вузькому секторі ϕ₁≤argα<ϕ₂. При цьому використовується зображення σa(n) у вигляді ряду за сумами Рамануджана. We construct an asymptotic formula for a sum function for σ a (α), where σ a (α) is the sum of the ath powers of the norms of divisors of the Gaussian integer α on an arithmetic progression α ≡ α₀ (mod γ) and in a narrow sector ϕ₁ ≤ arg α < ϕ₂. For this purpose, we use a representation of σ a (n) in the form of a series in the Ramanujan sums.